Impact of sea ice friction on ocean tides in the Arctic Ocean, modelling insights at various time and space scales - Mathilde Cancet; Florent H. Lyard; Ergane Fouchet (Ocean Modelling, 2025)

Understanding uncertainties in the satellite altimeter measurement of coastal sea level: insights from a round-robin analysis - Florence Birol; François Bignalet-Cazalet; Mathilde Cancet; Jean-Alexis Daguze; Wassim Fkaier; Ergane Fouchet; Fabien Léger; Claire Maraldi; Fernando Niño; Marie-Isabelle Pujol; Ngan Tran (Ocean Science, 2025)
The satellite radar altimetry record of sea level has now surpassed 30 years in length. These observations have greatly improved our knowledge of the open ocean and are now an essential component of many operational marine systems and climate studies. But the use of altimetry close to the coast remains a challenge from both a technical and scientific point of view. Here, we take advantage of the recent availability of many new algorithms developed for altimetry sea level computation to quantify and analyze the uncertainties associated with the choice of algorithms when approaching the coast. To achieve this objective, we did a round-robin analysis of radar altimetry data, testing a total of 21 solutions for waveform retracking, correcting sea surface heights and finally deriving sea level variations. Uncertainties associated with each of the components used to calculate the altimeter sea surface heights are estimated by measuring the spread of sea level values obtained using the various algorithms considered in the round-robin for this component. We intercompare these uncertainty estimates and analyze how they evolve when we go from the open ocean to the coast. At regional scale, complementary analyses are performed through comparisons with independent tide gauge observations. The results show that tidal corrections and uncertainties in the mean sea surface can be significant contributors to uncertainties in sea level estimates in many coastal regions. However, improving the quality and robustness of the retracking algorithm used to derive both the range and the sea state bias correction is today the main factor to bring accurate altimetry sea level data closer to the shore than ever before.

ALBATROSS: Advancing Southern Ocean tide modelling with high resolution and enhanced bathymetry - Eva Le Merle; Carole Belot; Ergane Fouchet; Mathilde Cancet; Ole Baltazar Andersen; Florent Lyard; Geir Moholdt; Michel Tsamados; Mahmoud El Hajj; Josephine Maton; Jérôme Benveniste; Marco Restano (Polar Science, 2024)

The new CNES-CLS18 global mean dynamic topography - Sandrine Mulet; Marie-Hélène Rio; Hélène Etienne; Camilia Artana; Mathilde Cancet; Gérald Dibarboure; Hui Feng; Romain Husson; Nicolas Picot; Christine Provost; P. Ted Strub (Ocean Science, 2021)
The mean dynamic topography (MDT) is a key reference surface for altimetry. It is needed for the calculation of the ocean absolute dynamic topography, and under the geostrophic approximation, the estimation of surface currents. CNES-CLS mean dynamic topography (MDT) solutions are calculated by merging information from altimeter data, GRACE, and GOCE gravity field and oceanographic in situ measurements (drifting buoy velocities, hydrological profiles). The objective of this paper is to present the newly updated CNES-CLS18 MDT. The main improvement compared to the previous CNES-CLS13 solution is the use of updated input datasets: the GOCO05S geoid model is used based on the complete GOCE mission (November 2009–October 2013) and 10.5 years of GRACE data, together with all drifting buoy velocities (SVP-type and Argo floats) and hydrological profiles (CORA database) available from 1993 to 2017 (instead of 1993–2012). The new solution also benefits from improved data processing (in particular a new wind-driven current model has been developed to extract the geostrophic component from the buoy velocities) and methodology (in particular the computation of the medium-scale GOCE-based MDT first guess has been revised). An evaluation of the new solution compared to the previous version and to other existing MDT solutions show significant improvements in both strong currents and coastal areas.

FES2014 global ocean tide atlas: design and performance - Florent H. Lyard; Damien J. Allain; Mathilde Cancet; Loren Carrère; Nicolas Picot (Ocean Science, 2021)
Since the mid-1990s, a series of FES (finite element solution) global ocean tidal atlases has been produced and released with the primary objective to provide altimetry missions with tidal de-aliasing correction at the best possible accuracy. We describe the underlying hydrodynamic and data assimilation design and accuracy assessments for the latest FES2014 release (finalized in early 2016), especially for the altimetry de-aliasing purposes. The FES2014 atlas shows extremely significant improvements compared to the standard FES2004 and (intermediary) FES2012 atlases, in all ocean compartments, especially in shelf and coastal seas, thanks to the unstructured grid flexible resolution, recent progress in the (prior to assimilation) hydrodynamic tidal solutions, and use of ensemble data assimilation technique. Compared to earlier releases, the available tidal constituent's spectrum has been significantly extended, the overall resolution has been augmented, and additional scientific byproducts such as loading and self-attraction, energy diagnostics, or lowest astronomical tides have been derived from the atlas and are available. Compared to the other available global ocean tidal atlases, FES2014 clearly shows improved de-aliasing performance in most of the global ocean areas and has consequently been integrated in satellite altimetry geophysical data records (GDRs) and gravimetric data processing and adopted in recently renewed ITRF standards (International Terrestrial Reference System, 2020). It also provides very accurate open-boundary tidal conditions for regional and coastal modelling.

SARAL/AltiKa Absolute Calibration from the Multi-Mission Corsica Facilities - Pascal Bonnefond; Pierre Exertier; Olivier Laurain; Amandine Guillot; Nicolas Picot; Mathilde Cancet; Florent Lyard (Marine Geodesy, 2015)